Objective Measure for Assessment of Speech Quality in Rooms - BRACHMAŃSKI, Stefan (Archives of Acoustics, 2008)
The methods for assessment of speech quality fall into two classes: subjective and objective methods. This paper includes an overview of the two methods of objective measurements speech intelligibility (Speech Transmission Index and the automatic speech recognition system (QE-ARM)). Experiments in which the methods were used are described. The results are compared with subjective measurements. Subjective and objective measurements were carried out in a room for different signal to noise (white and pink noise) ratio. The obtained results are shown as a curve describing a relation between a STI and signal to noise ratio (S/N) and STI versus logatom speech intelligibility.